Signal fires - Shapiro, Dani (New York : Penguin Random House LLC., 2023)
"Late on a summer night in 1985, three teenagers are in a tragic car crash on the quiet, suburban Division Avenue. A girl is killed, and Theo and Sarah Wilf are left with a devastating secret that will haunt their family forever. By the time the Shenkmans move in across the street, the accident has faded into the past, but secrets haunt both families and cause them to become intimately intertwined. When Waldo Shenkman, a brilliant but lonely child, befriends Ben Wilf, who is struggling with his wife's decline from Alzheimer's, he once again entangles the families' fates and sets in motion the spellbinding, unforgettable climax"--
Keywords: Novels